Age-related compositional and functional changes in the adult and breastfed buffalo rumen microbiome - Xu, Yixue; Feng, Tong; Ding, Zixu; Li, Ling; Li, Zhipeng; Cui, Kuiqing; Chen, Weihua; Pan, Hongping; Zhu, Peng; Liu, Qingyou (Frontiers in Microbiology, 2024)
The buffalo is an important domestic animal globally, providing milk, meat, and labor to more than 2 billion people of 67 countries. The rumen microorganisms of buffaloes play an indispensable role in enabling the healthy functionality and digestive function of buffalo organisms. Currently, there is a lack of clarity regarding the differences in composition and function of rumen microorganisms among buffaloes at different growth stages. In this study, metagenomics sequencing technology was applied to examine the compositional and functional differences of rumen microorganisms in adult and breastfed buffaloes.The results revealed that the rumen of adult buffaloes had significantly higher levels of the following dominant genera: Prevotella, UBA1711, RF16, Saccharofermentans, F23-D06, UBA1777, RUG472, and Methanobrevibacter_A. Interestingly, the dominant genera specific to the rumen of adult buffaloes showed a significant positive correlation (correlation>0.5, p-value<0.05) with both lignocellulose degradation-related carbohydrate-active enzymes (CAZymes) and immune signaling pathways activated by antigenic stimulation. The rumen of breastfed buffaloes had significantly higher levels of the following dominant genera: UBA629, CAG-791, Selenomonas_C, Treponema_D, Succinivibrio, and RC9. The rumen-dominant genera specific to breastfed buffaloes were simultaneously significantly positively correlated (correlation>0.5, p-value<0.05) with CAZymes associated with lactose degradation, amino acid synthesis pathways, and antibiotic-producing pathways. This indicates that the rumen microorganisms in breastfed buffaloes are more involved in the degradation of lactose and amino acids and antibiotic production.In conclusion, these findings suggest a close relationship between differences in rumen microbes and the survival needs of buffaloes at different growth stages.